How diet portfolio shifts combined with land-based climate change mitigation strategies could reduce climate burdens in Germany. (20th November 2022) - Chan, Katrina; Millinger, Markus; Schneider, Uwe A.; Thrän, Daniela
Abstract: Many studies have analysed the environmental impact of vegan, vegetarian, or reduced meat diets. To date, literature has not evaluated how diet shifts affect environmental impacts by utilising portfolios which reflect personal nutrition preferences. Further, changing diets could alter the available land for non-food uses. This paper defines novel diet portfolios to outline alternative diet transitions and choices within the population and finds their effect on greenhouse gas (GHG) emissions, primary energy use, and land use in Germany. The aim of this study is to capture how these diet shifts affect land availability and increase the options for land-based climate change mitigation strategies. To do so, a contextualisation is made to compare the use of freed-up land for afforestation or biomethane production (with and without carbon capture and storage). The investigated diet portfolios lead to a reduction of the investigated impacts (GHG emissions: 7–67%; energy use: 5–46%; land use: 6–64%). Additionally, afforestation of freed-up land from each diet portfolio leads to further emission removals of 4–37%. In comparison, using the land to produce energy crops for biomethane production could lead to 2–23% further CO 2 -eq emission reductions when replacing fossil methane. If biomethane production is paired with carbon capture and storage, emission abatement is increased to 3–34%. This research indicates various short-term pathways to reduce GHG emissions with portfolio diet shifts. Utilising freed-up land for climate change mitigation strategies could prove essential to meet climate targets, but trade-offs with, e.g. biodiversity and ecosystem services exist and should be considered. Highlights: Diet portfolios are used to represent realistic population diets. Diet portfolios include a mixture of 12 different diets. GHG emissions decrease by 67% if the population adopts a Vegan diet. Afforestation removes almost double the emissions compared to biomethane. BECCS has similar GHG abatement to afforestation.